Getting Good Outcomes from Sub-National Governments: A Case Study on Indonesian Fiscal Decentralisation - Hadiana, Ilham (Curtin University, 2020)
This thesis assesses Indonesia’s fiscal decentralisation policy from 2001 to 2018 and in particular its attempts at ensuring local government performance. These employed both methods suggested in the ‘second generation’ theory of fiscal federalism: constraints and incentives. The asymmetric approach to fiscal decentralisation policy is suggested as an alternative in accommodating diverse situations among local governments.